2015
DOI: 10.1007/s12035-015-9485-7
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin/Matrix Metalloproteinase-9-Dependent SK-N-SH Cell Migration is Mediated Through a PLC/PKC/MAPKs/NF-κB Cascade

Abstract: Thrombin has been known to activate inflammatory genes including matrix metalloproteinases (MMPs). The elevated expression of MMP-9 has been observed in patients with neuroinflammatory diseases and may contribute to the pathology of brain diseases. However, the mechanisms underlying thrombin-induced MMP-9 expression in SK-N-SH cells remain unknown. The effects of thrombin on MMP-9 expression were examined in SK-N-SH cells by gelatin zymography, Western blot, real-time PCR, promoter activity assay, and cell mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Previous studies have shown that LPS stimulates MAPK activation in various types of cells [50,51]. Moreover, our previous studies and others have indicated that Erk1/2, JNK1/2, and p38 MAPK could regulate MMP-9 induction in various types of cells [11,22,30]. In addition, MAPKs have been shown to be downstream components of PI3K/Akt in various cell types [11,22].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies have shown that LPS stimulates MAPK activation in various types of cells [50,51]. Moreover, our previous studies and others have indicated that Erk1/2, JNK1/2, and p38 MAPK could regulate MMP-9 induction in various types of cells [11,22,30]. In addition, MAPKs have been shown to be downstream components of PI3K/Akt in various cell types [11,22].…”
Section: Discussionmentioning
confidence: 84%
“…MAPKs play crucial roles in cellular functions, such as cell proliferation, differentiation, migration, senescence, and apoptosis [29]. Several reports have demonstrated that activation of MAPKs causes the expression of various inflammatory genes, including MMP-9 [11,30]. Therefore, we explored whether MAPKs contributed to the LPS-induced MMP-9 expression.…”
Section: Lps Induced Prommp-9 Expression Via Mapksmentioning
confidence: 98%
“…There have been several reports indicating that NF-κB can modulate MMP-9 expression mediated by various stimuli including LPS. 40,41 In this study, we also hypothesized that in RBA-1 cells, NF-κB was involved in LPS-mediated responses. We found that in RBA-1 cells, LPS can activate NF-κB activity through NOX/ROS signaling pathway to enhance MMP-9 expression.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, thrombin has been revealed to induce MMP-9 production related to pathological processes in various cell types [17,18,19]. In our previous studies, thrombin was shown to induce MMP-9 expression via various signaling components in SK-N-SH cells [20,21]. In the clinic, traditional Chinese medicines rich in flavonoids have been used to treat inflammatory diseases and prevent illnesses.…”
Section: Introductionmentioning
confidence: 99%